1997
DOI: 10.1074/jbc.272.28.17460
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Folic Acid Exporter Function with Markedly Augmented Folate Accumulation in Lipophilic Antifolate-resistant Mammalian Cells

Abstract: We previously described a 1,000-fold pyrimethamineresistant Chinese hamster ovary cell line (Pyr R100 ) which retains parental dihydrofolate reductase activity and methotrexate (MTX) sensitivity. This study characterizes the basis for the 14-fold decrease in folic acid and leucovorin concentrations required for clonogenic growth of Pyr R100 cells relative to parental AA8 cells. Under conditions in which folic acid reduction was blocked by trimetrexate, Pyr R100 cells displayed relative to parental AA8 cells a:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 32 publications
0
44
0
Order By: Relevance
“…Furthermore, antifolate drug activities are enhanced by decreased intracellular folates resulting from an hRFC genomic deletion (Zhao et al, 2004b,c;Chattopadhyay et al, 2006) or hRFC mutations (Zhao et al, 2000a). Conversely, antifolate effects are reduced by increased intracellular folates resulting from impaired efflux of folic acid (Assaraf and Goldman, 1997) or enhanced folic acid influx by a mutant RFC .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, antifolate drug activities are enhanced by decreased intracellular folates resulting from an hRFC genomic deletion (Zhao et al, 2004b,c;Chattopadhyay et al, 2006) or hRFC mutations (Zhao et al, 2000a). Conversely, antifolate effects are reduced by increased intracellular folates resulting from impaired efflux of folic acid (Assaraf and Goldman, 1997) or enhanced folic acid influx by a mutant RFC .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, short-time resistances to MTX seem to be related at least to the latter mentioned proteins. 26,[42][43][44][45][46][47][48] Although fundamental knowledge about the mechanisms that are involved in mediating MTX resistance is available, up to now, there is almost no understanding about the feasibility of hyperthermia for overcoming the heterogenic and unfavorable variation in MTX response in tumor cells. Moreover, despite the aforementioned advantages of using MNP for cancer treatment, the potential of MTX-MNP in overcoming the heterogenic cytotoxicity observed for free MTX, especially when combined with hyperthermia, is mostly unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Density was adjusted to 10 7 cells/ml in the same buffer. Transport measurements were performed as described previously (Assaraf and Goldman, 1997). Briefly, after 20-min incubation of cells at 37°C, uptake of [ 3 H]cholic acid (7600-8200 dpm/pmol) at a final concentration of 50 nM was initiated, after which 1-ml samples were drawn at the indicated times and transferred to centrifuge tubes containing 10 ml of ice-cold HEPES-buffered saline.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies demonstrated a marked loss of folate export activity in Pyr R100 cells, resulting in a substantial expansion in the intracellular folate pool (Assaraf and Goldman, 1997;Jansen et al, 1999). To explore the basis for the loss of folate efflux function, MRP1 through MRP5 and BCRP expression was examined in the microsomal fraction of wildtype AA8 and Pyr R100 cells (Fig.…”
Section: R100mentioning
confidence: 99%
See 1 more Smart Citation